Cultural Intelligence: A critical capability for health and safety professionals in building interpersonal trust? A literature Review. - Dearsly, Greg (New Zealand Journal of Health and Safety Practice, 2024)
This literature review was conducted as part of the authors submission in attaining a Master’s In Advanced Leadership Practices through Massey University (2018 – 2019). The literature review was supported with research which included focus groups, the aim of which was to explore the theories and beliefs of senior executives from the New Zealand business community about the impact of building trust where their health and safety advisor has cultural intelligence capability. It is intended that the results of the focus groups will be published in future issues of this publication.